Paracetamol (acetaminophen) with or without codeine or dihydrocodeine for neuropathic pain in adults - Wiffen, Philip J.; Knaggs, Roger; Derry, Sheena; Cole, Peter; Phillips, Tudor; Moore, R. Andrew (Wiley, 2016)
BACKGROUND